Proof of the Quantitative Potential of Immunofluorescence by Mass Spectrometry - Toki, Maria I. (Lab Invest, 2017)
Protein expression in formalin-fixed, paraffin-embedded (FFPE) patient tissue is routinely measured by Immunohistochemistry (IHC). However, IHC has been shown to be subject to variability in sensitivity, specificity and reproducibility, and is generally, at best, considered semi-quantitative. Mass spectrometry(MS) is considered by many to be the criterion standard for protein measurement, offering high sensitivity, specificity and objective molecular quantification. Here, we seek to show that quantitative immunofluorescence (QIF) with standardization can achieve quantitative results comparable to MS. Epidermal Growth Factor Receptor (EGFR) was measured by quantitative immunofluorescence in 15 cell lines with a wide range of EGFR expression, using different primary antibody concentrations, including the optimal signal-to-noise concentration after quantitative titration. QIF target measurement was then compared to the absolute EGFR concentration measured by Liquid Tissue selected reaction monitoring (LT-SRM) mass spectrometry. The best agreement between the two assays was found when the EGFR primary antibody was used at the optimal signal-to-noise concentration, revealing a strong linear regression (R(2) =0.88). This demonstrates that quantitative optimization of titration by calculation of signal-to-noise ratio allows QIF to be standardized to MS and can therefore be used to assess absolute protein concentration in a linear and reproducible manner.